The Analysis of Deixis Found in Channel New Asia - Nila Sari Haloho; Mhd Johan Johan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This article describes the study of pragmatics in a specific domain of deixis found in Channel New Asia. The aim of this study is to find out the type of deixis found in the Channel New Asia. In this research, through the discussion, it can be concluded from the Channel New Asia, based on Levinson and Yule theory, there are 4 types found and the function also found. From the 4th types, there are nine types of personal deixis. They are from the third person deixis. The use of she, there are three and the use of he, there are six. From the type of place deixis, there is one and also the same with discourse deixis is only one.